Pengaruh Promosi Kesehatan terhadap Tingkat Pengetahuan tentang Menstrual Hygiene pada Anak Usia 13–15 Tahun - Lilis Maghfuroh; Diah Eko Martini; Florensa Anna Wartama (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Menstrual hygiene is an important component of personal hygiene that plays a significant role in an individual's health behavior, helping to prevent disorders in reproductive organ function. This study aims to determine the effect of health promotion on the level of menstrual hygiene knowledge among children aged 13–15 years. The study design used a pre-experimental approach with a one-group pre-posttest design. The population consisted of 110 respondents, and using simple random sampling, 83 respondents were selected. Data for this study were collected using a knowledge level questionnaire. After tabulation, the data were analyzed using the Wilcoxon test with p < 0.05. The results showed that nearly all female students (108, or 98.2%) had insufficient knowledge of menstrual hygiene before receiving health promotion. Almost all female students after receiving health promotion had adequate knowledge of menstrual hygiene, totaling 88 (80.0%). Based on the above results, the effect of health promotion on the level of knowledge of menstrual hygiene among children aged 13-15 years was found to be p = 0.000 (p < 0.05). This indicates that health promotion has an effect on the level of knowledge about menstrual hygiene among girls aged 13–15 years. Therefore, it is hoped that female students will always maintain their genital hygiene by practicing proper personal hygiene in accordance with the guidelines provided by healthcare professionals, especially during menstruation.